Business Model Innovation in Research and Development: State of the Art and Based on Public Needs - Brian Pratistha (The Journal of Indonesia Sustainable Development Planning, 2022)
Every institution has business models, but some are not properly realized to benefit and meet the public needs. The aim of the study was to improve the government's existing business models in space technology to meet the public needs. Related studies regarding the issues were reviewed, and personal observation was conducted at the government space institution in Indonesia. The study found that to attain the public needs, the development of the business model in space technology should consider four aspects, research and development expenditures, wellbeing, sustainable cities and communities, and adoption of emerging technologies. Incorporating the four aspects into the existing business model is expected to bring the research and development closer to what the public wants.